Cardiac Rehabilitation in Heart Failure: Looking Further Ahead. Issue 1 (2019) - Vilela, Eduardo M; João, Ana; Fonseca, Marlene; Sampaio, Sampaio; Torres, Susana; Ladeiras-Lopes, Ricardo; ,; Campos, Lilibeth; Caeiro, Daniel; Fontes-Carvalho, Ricardo; ,; Silva, Marisa; et al.
No abstract available